2010
DOI: 10.3390/molecules15042872
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Adsorption Performance of a Novel Anionic Starch Microsphere

Abstract: Neutral starch microspheres (NSMs) were synthesized by an inverse microemulsion technology with epichlorohydrin as a crosslinker and soluble starch as starting material. Anionic starch microspheres (ASMs) were prepared from NSMs by the secondary polymerization with chloroacetic acid as the anionic etherifying agent. Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and laser diffraction particle size analyzer were used to characterize the anionic starch microspheres. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 38 publications
(33 reference statements)
2
17
0
1
Order By: Relevance
“…The phenomenon of aggregation was mainly attributed to the results of the emulsification and cross-linking process. Previous studies [14,20] reported that the size distribution of the droplets in the emulsion was wide when emulsified by mechanical stirring, which led to the aggregation and breakup of droplets during the emulsification and cross-linking process. So, the phenomenon of aggregation between SDM-Ms would appear.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of aggregation was mainly attributed to the results of the emulsification and cross-linking process. Previous studies [14,20] reported that the size distribution of the droplets in the emulsion was wide when emulsified by mechanical stirring, which led to the aggregation and breakup of droplets during the emulsification and cross-linking process. So, the phenomenon of aggregation between SDM-Ms would appear.…”
Section: Resultsmentioning
confidence: 99%
“…Starch, one of the most abundant renewable resources in the world has been investigated as an adsorbent to remove water pollutants [18][19][20][21]. For instance, Guo et al [22] synthesized a crosslinked porous starch and found that its adsorption capacity of product for methylene blue (MB) can reach 9.46 mg g −1 , which was much higher than that of native starch.…”
Section: Introductionmentioning
confidence: 99%
“…They argued that any increase in the temperature beyond the optimum temperature decreased the surface activity of the adsorbent . Yang et al also found a similar endothermic–exothermic driven adsorption of methylene blue (cationic dye like BG) on starch material. The methylene blue adsorption process was endothermic at T ≤ 30°C but it became exothermic at >30°C up to 60°C.…”
Section: Resultsmentioning
confidence: 93%